SIDEROPHILE GEOCHEMISTRY OF GA, GE, AND SN: CATIONIC OXIDATION STATES IN SILICATE MELTS AND THE EFFECT OF COMPOSITION IN IRON-NICKEL ALLOYS - THE EFFECTS OF PRESSURE, TEMPERATURE, OXYGEN FUGACITY, AND SILICATE AND METALLIC MELT COMPOSITIONS - Capobianco C.J.; Drake M.J.; de'Aro J. (My University, 1999)
We report a series of metal-silicate partitioning experiments for Ga, Ge, and Sn to characterize the dependence of the partition coefficient, D, on oxygen fugacity, fO2. These were isothermal (1260°C) and isobaric (1 bar) experiments using a silicate composition that approximates a eucritic meteorite. It is well known that elements such as Ni, which exist in only one valence state under redox conditions of planetary interest, produce linear trends on log D vs log fO2 diagrams. For our experiments on Ga, Ge, and Sn, however, large deviations from linearity were evident and seemed to suggest unusual changes in the oxidation states for these elements in the silicate melt. But such an inference would have been mistaken because the metallic phase of these experiments, Ni-Fe alloys, was not of constant composition; instead, the Ni/Fe ratio was varied systematically to control oxygen fugacity. Although Ni and Fe form alloys that are not far from ideal, binary interactions between the trace elements and either major metallic component, Ni or Fe, are not necessarily similar.Using only information obtained from the literature on binary mixing properties among the metallic components, Fe, Ni, Ga, Sn, and Ge, a simple thermodynamic solution model was formulated to calculate the activity coefficients for the metallic components in our experimental system. It was found that, despite the slight deviations from ideality for Ni-Fe alloys, large differences exist between the way Ni interacts with trace elements and the way Fe does. Activity coefficients calculated from the thermodynamics of the metallic solution rationalized the experimentally derived log D vs log fO2 plots. When the independently derived activity coefficients for the trace elements in the alloys (γ) are used to plot log γ KD vs log fO2, the unusual oxygen fugacity dependencies can be fully reconciled with the expected valences of 3+ for Ga, 4+ for Ge, and predominantly 4+ at high oxygen fugacities changing to predominantly 2+ at low oxygen fugacities for Sn. If a planetary metal-silicate system evolves with increasing oxygen fugacity, the increasing Ni content of the metal will maintain the siderophile character of Ga, Ge, and Sn because these elements are more stable dissolved in Ni compared to Fe.